Konsep Membangun Generasi “Tafaqquh Fid Din” di Pesantren Persatuan Islam (Persis) Cikarang Utara Kabupaten Bekasi - Wahidin; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic Unity or remembered PERSIS is an Islamic organization according to Deliar Noer above as an Islamic organization that has a modern movement in the educational and social fields. Although the Islamic Union was born on September 12, 1923, it was only around the 1930s that the Islamic Union had a formal educational institution called